2022
DOI: 10.1002/jper.22-0249
|View full text |Cite
|
Sign up to set email alerts
|

Association between total body bone mineral density and periodontitis: A Mendelian randomization study

Abstract: Background:The purpose of the study was to examine the association between total body bone mineral density (BMD) and periodontitis using Mendelian randomization (MR) analysis. Methods and materials:We used 81 single nucleotide polymorphisms (SNPs) associated with BMD at a p-value of < 5 × 10 −8 from a genome-wide association study (GWAS) of 66,628 individuals of European descent. The GWAS for periodontitis was derived from a meta-analysis of seven cohort studies that included 17,353 cases and 28,210 controls o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The sensitivity analyses did not indicate weak instrument bias and substantial pleiotropy that could bias the MR estimates. Our findings are in support of a previous MR study showing a null association of total body BMD with periodontitis (Alayash et al, 2022). Taken together, our results suggest that the previously observed associations could have been contributed by unmeasured confounders.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The sensitivity analyses did not indicate weak instrument bias and substantial pleiotropy that could bias the MR estimates. Our findings are in support of a previous MR study showing a null association of total body BMD with periodontitis (Alayash et al, 2022). Taken together, our results suggest that the previously observed associations could have been contributed by unmeasured confounders.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, MR also found no evidence supporting the association of cannabis use, depression, psoriasis, and vitamin D level with periodontitis, contradicting the epidemiological findings (Baumeister, Alayash, et al, 2022; Baumeister, Reckelkamm, et al, 2022; Baurecht et al, 2022; Nolde et al, 2022). A recent MR study found a null association of total body BMD with periodontitis (Alayash et al, 2022). Although osteoporosis is a systemic disease, the forearm, femoral neck, lumbar spine, and heel are prevalent skeletal sites with decreased BMD (Stone et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…There is also supporting evidence from Mendelian randomization studies, which indicate no causal effect of osteoporosis on periodontitis. 36,37 The discrepancy of the impact of functional thyroid disease on periodontitis may be due to the failure of sufficient adjustment for confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Although MR cannot replace RCTs, it can provide complementary information. 11,12 There are several MR studies that have reported the causal association between different complement components and certain diseases such as deep vein thrombosis, 13 ischemic stroke, 14 periodontitis, 15 multiple myeloma, 16 chronic prostatitis, 17 and Alzheimer's disease. 18 As establishing a causal relationship for the effect of complement components in causing liver diseases can be challenging due to the aforementioned reasons (e.g., inverse causality), MR studies can be useful in this regard.…”
Section: Editorialmentioning
confidence: 99%